2022
DOI: 10.3389/fped.2022.1036306
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease following SARS-CoV-2 infection: Stronger inflammation with no increase in cardiac complications

Abstract: BackgroundHerein we investigate the difference between Kawasaki disease (KD) with and without a recent history of SARS-CoV-2 infection.MethodsWe compared the clinical characteristics of patients with KD during the SARS-CoV-2 pandemic in a single children's hospital in Korea. Fifty-two patients were enrolled and divided into group 1 (with a history of COVID-19, n = 26) and group 2 (without a history of COVID-19, n = 26) according to whether or not they contracted COVID-19 within the 8 weeks before hospitalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…All the patients included in the present study were discharged with a diagnosis of KD, moreover, four expert clinicians, two paediatric immunologists and two paediatric cardiologists, analysed the cases to include to better discriminate between the two diagnoses. A Korean study did not find differences in cardiac complications between patients with KD with and without a recent COVID-19 infection [27]. Since in our sample, only five patients had recent or concurrent SARS-CoV-2 infection, we did not evaluate the differences between the two groups.…”
Section: Discussionmentioning
confidence: 79%
“…All the patients included in the present study were discharged with a diagnosis of KD, moreover, four expert clinicians, two paediatric immunologists and two paediatric cardiologists, analysed the cases to include to better discriminate between the two diagnoses. A Korean study did not find differences in cardiac complications between patients with KD with and without a recent COVID-19 infection [27]. Since in our sample, only five patients had recent or concurrent SARS-CoV-2 infection, we did not evaluate the differences between the two groups.…”
Section: Discussionmentioning
confidence: 79%
“…Roh et al. ( 70 ) found that the number of KD patients with COVID-19 receiving IFX was higher than those KD patients without a history of COVID-19 (two patients vs none), but it was not statistically significant. Therefore, the exact roles of IFX in treating KD patients with COVID-19 and patients with MIS-C still need further investigation.…”
Section: Roles Of Tnf-α Antagonist (Ie Ifx) In Kd Patients With Sars-...mentioning
confidence: 95%
“…Due to IFX is a TNF-a antagonist, patients with MIS-C might be successfully treated with IFX (69). For the KD patients with SARS-CoV-2 infection, Roh et al (70) reported that post-COVID KD showing a stronger inflammatory response than KD-alone, but with no differences in cardiac complications. Limited studies have shown the efficacy of IFX in treating KD patients with SARS-CoV-2 infection.…”
Section: Infusion Reactionmentioning
confidence: 99%
“… 53 , 78 It is possible that some of the decrease in KD may be related to misclassification of KD patients as having MIS-C, although this is more likely related to decrease exposure to possible infectious/environmental triggers. 79 , 80 A case series from Korea, where the incidence of MIS-C during the pandemic has been very low, compared 19 KD patients with a history of prior COVID-19 with 26 KD patients without, and noted few differences, although patients with prior COVID were older with more severe disease, which may suggest some similiarities with MIS-C. 81 The association of prior COVID-19 and vaccination with the risk of subsequent KD is largely unknown. In contrast, a report from Seattle noted that patients with a prior history of KD did not have adverse outcomes when either infected with SARS-CoV-2 or vaccinated with mRNA COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%